Enzymatic mediated modification of gum Arabic by curcumin oxidation products: Physicochemical and self-assembly study. (May 2022) - Adam, Aurélie A.; Jasniewski, Jordane; Vuillemin, Marie E.; Simard, Blandine; Burgain, Jennifer; Badin, Régis; Muniglia, Lionel; Michaux, Florentin
Abstract: Gum Arabic (GA) is a polysaccharide widely used in industry as an emulsifier and encapsulating agent. Nevertheless, its physicochemical properties can be largely improved. The objective of this study was then to modify its structure to improve its functionalities or to provide new ones. To do so, a heterogeneous catalysis process using a laccase and a phenolic compound, curcumin, in aqueous solution was performed. The laccase allowed the oxidation of curcumin, which was then able to be grafted onto the polymer. Therefore, this environmentally friendly process allowed the modification of GA with curcumin oxidation products (OXP) by creating ester bonds between GA and OXP. The molecular mass of GA was largely increased after functionalization. This product contained two fractions of approximately ∼1.165 × 10 8  g.mol −1 and ∼5.057 × 10 6  g.mol −1 . All these modifications impacted greatly the polymer properties such as its thermal behaviour, with a significant decrease of its glass transition, its hydrophilicity and its hygroscopicity. They also brought antioxidant properties to the modified GA. Moreover, the modification led interestingly to the spontaneous formation of spherical monodisperse micrometric particles in water. Graphical abstract: Image 1 Highlights: - The laccase assisted modification of gum Arabic by curcumin oxidation allowed the grafting of phenolic compounds. - Contrary to the native one, modified gum Arabic presented a phase transition temperature. - Due to a higher hydrophobicity, modified gum Arabic formed spherical particles in water.